Critical Information Infrastructure Security 6th International Workshop, CRITIS 2011, Lucerne, Switzerland, September 8-9, 2011, Revised Selected Papers - Bologna, Sandro.; Hm̃merli, Bernhard.; Gritzalis, Dimitris.; Wolthusen, Stephen. (Lecture Notes in Computer Science,, 2013)
This book constitutes revised selected papers from the 6th International Workshop on Critical Information Infrastructure Security, CRITIS 2011, held in Lucerne, Switzerland, in September 2011. The 16 full papers and 6 short papers presented in this volume were carefully reviewed and selected from 38 submissions. They deal with all areas of critical infrastructure protection research.